2016
DOI: 10.3390/ijms17081193
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and Toxicity of Superparamagnetic Iron Oxide Nanoparticles in Cells and Experimental Animals

Abstract: The uptake and distribution of negatively charged superparamagnetic iron oxide (Fe3O4) nanoparticles (SPIONs) in mouse embryonic fibroblasts NIH3T3, and magnetic resonance imaging (MRI) signal influenced by SPIONs injected into experimental animals, were visualized and investigated. Cellular uptake and distribution of the SPIONs in NIH3T3 after staining with Prussian Blue were investigated by a bright-field microscope equipped with digital color camera. SPIONs were localized in vesicles, mostly placed near the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 38 publications
1
48
0
1
Order By: Relevance
“…The viability percentage recorded was above 80% in all cases which shows the high cytocompatibilty of the nanoparticles towards the fibroblast cells. Similar results for non toxicity of iron oxide nanoparticles synthesized against NIH 3T3 fibroblast cell line were reported [49]. The biocompatibility of the synthesized iron oxide nanoparticles on erythrocyte cells was investigated.…”
Section: Cytocompatibility Using Mtt Analysis and Haemolytic Activitysupporting
confidence: 77%
“…The viability percentage recorded was above 80% in all cases which shows the high cytocompatibilty of the nanoparticles towards the fibroblast cells. Similar results for non toxicity of iron oxide nanoparticles synthesized against NIH 3T3 fibroblast cell line were reported [49]. The biocompatibility of the synthesized iron oxide nanoparticles on erythrocyte cells was investigated.…”
Section: Cytocompatibility Using Mtt Analysis and Haemolytic Activitysupporting
confidence: 77%
“…MOFs offer several advantages over current DDSs, which are often purely organic or inorganic. The former (liposomes or polymers), although more biocompatible, usually present lower drug payloads [17][18][19], while the latter (gold, iron and silica nanoparticles among others), can offer notably higher drug loadings but are less biocompatible, and their low degradation rate can result in accumulation in the liver or spleen, potentially inducing unwanted side effects (Figure 1) [20][21][22]. The organic/inorganic nature of MOFs has positioned them as an attractive alternative to the drawbacks that nanomedicine is currently facing, as it offers almost unlimited possibilities to design desired structures through metal-linker chemistry and postsynthetic modification in order to enhance their drug delivery properties, such as high drug loadings, controllable release of the drug, low cytotoxicity, appropriate colloidal stability and degradation rates, efficient cell internalisation, and anticancer cell selectivity [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Discussion on biological issues related to the biocompatibility, toxicity, etc. are outside the scope of this short review and can be found elsewhere [106][107][108][109][110][111]. While the present review offers a brief introduction to the topic, interested readers can find comprehensive reviews published recently [112][113][114][115][116][117].…”
Section: Discussionmentioning
confidence: 99%